Pelatihan Penguatan Peran dan Fungsi Posyandu dalam Rangka Ketahanan Kesehatan Keluarga di Kecamatan Panton Reu, Aceh Barat - Bartoven Vivit Nurdin; yulianto Yulianto; Hartoyo Hartoyo; Noverman Duadji; Zellya Salsabila (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2026)
This community service activity aims to provide training to strengthen the role and function of Posyandu in improving community health resilience in Panton Reu Subdistrict, West Aceh. Panton Reu is an area with a high stunting rate in Aceh and was affected by the tsunami disaster. In addition, many residents still lack awareness of the importance of bringing infants to posyandu, especially for immunization. To address this issue, APPSI together with the Faculty of Social and Political Sciences of Teuku Umar University and Lampung University conducted training using socio-cultural approaches through family sociology and health anthropology perspectives. The activity involved communities and posyandu cadres through socialization, training, and mentoring. The results showed an increase in participants’ understanding of the role and function of posyandu, indicated by the increase in average pre-test and post-test scores from 7.3 to 9.6. Participants also showed active involvement in improving family health resilience and stunting prevention. The outputs include journal publications, seminar presentations, videos, and activity reports.